PENGEMBANGAN MULTIMEDIA PEMBELAJARAN UNTUK MATAKULIAH GRAFIK KOMPUTER MENGGUNAKAN METODE ADDIE - Yuniansyah Yuniansyah; Andri Saputra (Universitas Bumigora, 2017)
This research aims to develop multimedia learning in computer graphics courses. The development method used is ADDIE (Analysis Design Develop Implementation Evaluate) which is a method usually used for the development of multimedia learning. The process of analysis is done by looking and studying the process of teaching and learning that runs during this, at the design stage used Adobe Photoshop software. In the process of developing the author using Adobe Flash CS6 for display, writing and animation, as well as Visual camtasia video creation. After the development process is complete, the implementation stages are tested using white box and black box test method. In evaluation prooses involving multimedia experts and students who have followed or are following the course of Computer Graph. Based on the results of experiments and evaluations can be concluded that multimedia learning Graphics Data meet the criteria very well include operational aspects and teaching materials and can be used to help students and lecturers on teaching and learning process, and can be used by students to learn independently.